Pengaruh Kualitas Pelayanan Kefarmasian terhadap Kepuasan Pasien Rawat Inap RSUP Dr. M. Djamil Padang - Linda Eka Putri; Dachriyanus; Nilda Tri Putri (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2018)
Pharmaceutical services at the hospital are an integral part of the hospital's service system. The quality of the pharmacy service affects the hospital's performance as a service company. Pharmacy Installation of Dr. M. Djamil Padang Hospital based on data from Public Relation and Public Complaint Installation of Dr. M. Djamil Padang Hospital get complaint report on pharmacy service as many as 28 complaint reports in 2015 and 42 complaint reports in 2016. A decrease in the quality of care is indicated by the decrease in the number of in-patients in the period of 2013-2015 reaching an average of 2.89%, while the level of complaints on the quality of in-patient pharmacy service remains high with 31 complaints by years. This study aims to analyze the effect of hospital pharmacy service quality on patient satisfaction at pharmacy depo Dr. M. Djamil Padang Hospital. The measurements of all constructs and research indicators used questionnaires distributed to 320 in-patients as respondents. Path analysis used with software application of SPSS 17 to analyze the data. The result concluded that service quality consisting of service speed, attitude, and empathy of officer, drug availability, pharmacy depot location, and drug information simultaneously, influence on patient's satisfaction with a contribution of 74.10%. However, the partial attitude and empathy of the officers have no effect on the satisfaction of patients. While the provision of drug information is the most dominant factor of service quality in affecting patient satisfaction at pharmacy depo Dr. M. Djamil Padang Hospital.